Dysregulation of saliva and fecal microbiota as novel biomarkers of colorectal cancer - Rong, Jiamei; Chen, Xiaocui; Li, Zhangqin; Li, Bona; Sun, Yang; Miao, Yinglei (Frontiers in Oncology, 2024)
The aim of this study was to investigate the biomarkers of salivary and fecal microbiota in Colorectal cancer (CRC). Initially, the study scrutinized the microbial community composition disparities among groups. Utilizing Lasso analysis, it sifted through operational taxonomic units (OTUs) to pinpoint distinctive features. Subsequently, by intersecting feature OTUs across groups, it curated a set of core-shared OTUs and devised a corresponding network. Concluding with functional enrichment analysis, the research delved into the divergent biological functions of these microbial communities within the studied groups. Analysis revealed higher bacterial diversity in saliva compared to feces, with distinct differences at both phylum and genus levels. Feces primarily contained Firmicutes, while saliva was dominated by Bacteroidetes and Proteobacteria. Notably, Escherichia-Shigella and Fusobacterium in feces and Streptococcus in saliva showed increasing abundance from average to adenoma to colorectal cancer. Specific dominant flora was identified within and between groups, including CRC and adenomas across different stages. Seventeen core shared OTUs were identified, and networks of shared OTUs were constructed for each group. Functional enrichment analysis highlighted distinct microbial community functions among the groups. This study’s findings on characteristic OTUs in saliva and fecal samples offer valuable insights for distinguishing between healthy individuals, adenoma patients, and those with colorectal cancer. This study identified distinctive OTUs in saliva and feces to distinguish between healthy individuals, adenoma patients, and those with CRC, offering a valuable diagnostic reference.